2015
DOI: 10.1007/s10549-015-3569-y
|View full text |Cite
|
Sign up to set email alerts
|

The clinical significance of internal mammary lymph node (IMLN) biopsy during autologous reconstruction in breast cancer patients

Abstract: The clinical significance of IMLN metastases in breast cancer is controversial. Although IMLN status is an integral part of current AJCC staging of breast cancer, the elective sampling of IMLN is not part of routine surgery for breast cancer. The purpose of this study was to determine the incidence of IMLN metastases, associated risk factors if any, and its impact on further management and outcome. We retrospectively studied 470 cases that underwent autologous reconstruction surgery between 2002 and 2014. Of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…The prevalence detected by imaging was 2.4% for US, 21 1.2% for combined MRI and PET/CT, 22 9.5% for MRI, and 4.8% for PET/CT 23 . Studies including data from IMN biopsy during FFR found a prevalence ranging from 3.6% to 13.9% 24–26 …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The prevalence detected by imaging was 2.4% for US, 21 1.2% for combined MRI and PET/CT, 22 9.5% for MRI, and 4.8% for PET/CT 23 . Studies including data from IMN biopsy during FFR found a prevalence ranging from 3.6% to 13.9% 24–26 …”
Section: Resultsmentioning
confidence: 96%
“…Indeed, several previous studies have argued that there is a benefit associated with IMN biopsy during both immediate and delayed FFR 54–62 . Three studies examined data collected in this setting 24–26 . A major limitation in comparing the studies is heterogeneity of patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…The status of IMN can influence the clinical pathway of breast cancer patients because IMN metastases in breast cancer patients are associated with poor prognosis (9). Pathological confirmation of LNs prior to definitive therapy is important, because normal IMNs may appear incidentally on MRI or PET scans due to physiologic change (10)(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…When using a free flap for immediate autologous reconstruction after mastectomy, the internal mammary artery (IMA) and IMV are the preferred recipient vessels because of their large caliber and high flow rate, which provides a reasonable opportunity to study IMLN metastasis. Recent studies have identified that 3.6-6% of breast cancer patients have positive IMLNs based on biopsy performed during immediate reconstruction after mastectomy [48][49][50]. However, among 2057 patients who underwent free-flap breast reconstruction, Ochoa et al [51] found that only 28 patients (1.3%) had positive IMLNs, and the preoperative breast MRI provided 11% sensitivity for detecting the IMLN.…”
Section: Histopathologically Confirmed Imln Metastasismentioning
confidence: 99%
“…However, a pathological diagnosis (are intercostal space IMN biopsy or endoscopic lymphatic chain resection) is still important for determining IMLN metastasis, as the pathological LN stage may change in a subset of patients, who may then require a revised treatment strategy [ 9 , 46 ]. Although the pathological determination of IMLN status remains important, the performance of intercostal space IMN biopsy and endoscopic lymphatic chain resection remains controversial because these techniques are not associated with improvements in survival or in intraoperative/postoperative complications [ 13 , 47 , 48 ]. Thus, IMLN dissection is not routinely recommended.…”
Section: Imln Metastasis In Newly Diagnosed Patientsmentioning
confidence: 99%